Effects of TiO2 content and thermal parameters on crystallization kinetics and mechanical properties of phosphate based glass system - Pratthana Intawin (2020)
© 2020 Elsevier B.V. The effects of TiO2 content and thermal parameters on crystallization kinetics and mechanical properties of sodium-calcium-phosphate glass system have been revealed in this study. From the DTA results using for crystallization kinetics study, the activation energies of crystallization and Avrami parameters have been calculated. The glass transition (Tg), crystallization temperature (Tp) and activation energy (E) were found to increase with the increase in the content of TiO2. The major crystalline phases were calcium pyrophosphate and sodium dititanium triphosphate along with rutile as the minor crystalline phase presented as phase separation in the samples. Mechanical properties were obtained from the microhardness measurements for all samples. It was found that the added TiO2 content caused positive effect while heat treatment temperature caused negative effect on Young's modulus, Knoop hardness and Vickers hardness.